Activation of hypoactive parvalbumin-positive fast-spiking interneurons restores dentate inhibition to reduce electrographic seizures in the mouse intrahippocampal kainate model of temporal lobe epilepsy - Sang-Hun Lee; Young-Jin Kang; Bret N. Smith (Neurobiology of Disease)
Parvalbumin-positive (PV+) GABAergic interneurons in the dentate gyrus provide powerful perisomatic inhibition of dentate granule cells (DGCs) to prevent overexcitation and maintain the stability of dentate gyrus circuits. Most dentate PV+ interneurons survive status epilepticus, but surviving PV+ interneuron mediated inhibition is compromised in the dentate gyrus shortly after status epilepticus, contributing to epileptogenesis in temporal lobe epilepsy. It is uncertain whether the impaired activity of dentate PV+ interneurons recovers at later times or if it continues for months following status epilepticus. The development of compensatory modifications related to PV+ interneuron circuits in the months following status epilepticus is unknown, although reduced dentate GABAergic inhibition persists long after status epilepticus. We employed whole-cell patch-clamp recordings from dentate PV+ interneurons and DGCs in slices from male and female sham controls and intrahippocampal kainate (IHK) treated mice that developed spontaneous seizures months after status epilepticus to study epilepsy-associated changes in dentate PV+ interneuron circuits. Electrical recordings showed that: 1) Action potential firing rates of dentate PV+ interneurons were reduced in IHK treated mice up to four months after status epilepticus; 2) spontaneous inhibitory postsynaptic currents (sIPSCs) in DGCs exhibited reduced frequency but increased amplitude in IHK treated mice; and 3) the amplitude of IPSCs in DGCs evoked by optogenetic activation of dentate PV+ cells was upregulated without changes in short-term plasticity. Video-EEG recordings revealed that IHK treated mice showed spontaneous electrographic seizures in the dentate gyrus and that chemogenetic activation of PV+ interneurons abolished electrographic seizures. Our results suggest not only that the compensatory changes in PV+ interneuron circuits develop after IHK treatment, but also that increased PV+ interneuron mediated inhibition in the dentate gyrus may compensate for cell loss and reduced intrinsic excitability of dentate PV+ interneurons to stop seizures in temporal lobe epilepsy.